GAYA KEPEMIMPINAN KEPALA SEKOLAH PADA KINERJA GURU DI SMP NEGERI 27 BANDAR LAMPUNG - Tommy Ardiansyah; Fisman Bedi; Ahmad Fauzan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Educational success depends on leadership. Schools can move towards improving quality and service if the principal chooses the right leadership style. The purpose of this study is to provide a description and analysis of the principal's leadership style at SMP Negeri 27 Bandar Lampung in an effort to improve the performance of teachers and education personnel, and to examine the factors that influence the principal's leadership style. This research uses a qualitative approach, namely field research, where data is collected in the field to see phenomena in a natural environment. The data collection methods used in this research are interviews or interviews, observation, and documentation. Researchers used the Triangulation technique to test the validity of the data. The results of the study include several leadership styles: (1) democratic leadership; (2) autocratic leadership; (3) bureaucratic leadership; (4) charismatic leadership; (5) transformational; and (6) transactional leadership.